An ELISA for quantification of recombinant human EGF in production process samples, serum and urine. (January 2018) - Leyva, Alberto; Santana, Hector; Font, Milagros; Pérez, Barbara; Valdés, Rodolfo
Abstract: A sandwich enzyme-linked immunosorbent assay for quantifying a recombinant human Epidermal Growth Factor (rhEGF) protein used in a vacunal preparation is described. The protein was detected with high specificity in a short incubation time at elevated temperature, the assay showing a linear range between 0.0625 and 1 ng/mL. According to the regression analysis for the dilutional linearity data, r 2  = 0.9998, slope = 1.07 and intercept = 0.05 were obtained. The intra- and inter-assay coefficient of variation, ranged from 0.79 to 2.87% and 4.87–9.69% respectively demonstrating high reproducibility and precision. The ANOVA test used in the specificity/interference study revealed parallelism among curves (p > 0.1), which indicated lack of interference in the working range. Recovery obtained in accuracy test for three concentration levels varied between 89 and 111%; evidencing a reliable analytical assay to characterize the quality of the recombinant protein in the manufacturing process at large scale, and other biological matrixes as: urine and serum.